2003
DOI: 10.1046/j.1442-2042.2003.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hypertension on lower urinary tract symptoms in benign prostatic hyperplasia

Abstract: Aim : To clarify the influence of hypertension on lower urinary tract symptoms (LUTS) we examined the relationship between blood pressure, LUTS, and the effect of terazosin on LUTS in patients with benign prostatic hyperplasia (BPH). Methods : The subjects were patients who had LUTS and BPH. They were treated with terazosin (1 mg, twice-a-day) for 12 weeks. Calculation of the International Prostate Symptom Score (IPSS), measurement of blood pressure, and uroflowmetry were performed before and after 12 weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 19 publications
(28 reference statements)
2
43
2
5
Order By: Relevance
“…A previous study showed that hypertensive BPH patients have more severe LUTS than normotensive BPH patients, and that hypertension worsens LUTS and may reduce the efficacy of terazosin 2. However, in the present study, clinical parameters at baseline were similar in the two study groups.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…A previous study showed that hypertensive BPH patients have more severe LUTS than normotensive BPH patients, and that hypertension worsens LUTS and may reduce the efficacy of terazosin 2. However, in the present study, clinical parameters at baseline were similar in the two study groups.…”
Section: Discussioncontrasting
confidence: 74%
“…However, alpha1-adrenoceptor antagonists are not first-line therapies for hypertension, and the majority of hypertensive BPH patients will be receiving other antihypertensive agents that may increase the risk of drug interactions and side-effects. In addition, hypertension may reduce the effect of an alpha1-adrenoceptor antagonist on lower urinary tract symptoms (LUTS) 2. Furthermore, although 5 or 10 mg terazosin daily been routinely used in North America and Europe, terazosin is equally effective for treating symptomatic BPH in Asian patients at lower doses than those used in the West 3-5.…”
Section: Introductionmentioning
confidence: 99%
“…We also found a significant association between nocturia and non-dipping in patients with BPH. We believe that the difference observed between the two groups (20) was due to the presence or absence of nocturia or BPH. Accordingly, we suggest that increased sympathetic activity may be a common pathophysiological factor for non-dipping and nocturia.…”
Section: Discussionmentioning
confidence: 77%
“…A retrospective analysis [19] of 9857 men with BPH revealed that symptoms of BPH were more frequent in hypertensive patients. In another study by Sugaya et al [20], it was found that hypertension may worsen LUTS. Our groups were well matched with regard to their hypertension status, with similar percentages of hyper-and normotensive subjects in each group.…”
Section: Discussionmentioning
confidence: 96%
“…Premenopausal women are considered to be protected from HT relative to age‐matched men, but this protection is lost after the onset of menopause . The majority of female OAB patients are elderly, and HT is hypothesized to be a risk factor for developing OAB …”
Section: Discussionmentioning
confidence: 99%